Shear Wave Elastography (SWE) for the Evaluation of Patients with Plantar Fasciitis - Gatz, Matthias; Bejder, Ljudmila; Quack, Valentin; Schrading, Simone; Dirrichs, Timm; Tingart, Markus; Kuhl, Christiane; Betsch, Marcel (Academic Radiology, 2020)
Rationale and Objectives: The current imaging standard for diagnosing plantar fasciitis is B-Mode ultrasound (B-US). The aim of this study was to determine the diagnostic potential of Shear Wave Elastography (SWE) and the correlation of clinical scores to elastographic parameters. Materials and Methods: Diagnostic case-control study with n = 82 plantar fascia (PF). PF were divided into three subgroups: (1) symptomatic PF (n = 39); (2) control group of unilateral asymptomatic PF (n = 23); (3) bilateral asymptomatic PF (n = 20). Reference standard for positive findings in B-US was a PF thickness greater than 4 mm. For SWE tissue elasticity (Young's modulus kPa; shear wave speed m/s) was measured at Location 1: directly at the calcaneus; Location 2: +1 cm distal of the calcaneus and Location 3: central part of the calcaneus. Sensitivity, specificity, and diagnostic accuracy as well as correlation to American Orthopaedic Foot and Ankle Score (AOFAS) and Food Functional Index (FFI) were determined. Results: Symptomatic PF are thicker (4.2 mm, n = 39) than asymptomatic (3.0 mm, n = 43) (p < 0.001). Thickness of the PF (n = 82) correlated poorly to clinical scores (p = 0.001): FFI-pain (r = 0.349); FFI-function (r = 0.381); AOFAS (r = −0.387). Cut-off point for positive SWE finding was 51.5 kPa (4.14 m/s). Symptomatic PF (31.9 kPa, 3.26 m/s, n = 39) differ significantly from asymptomatic PF (93.3 kPa, 5.58 m/s, n = 43) with significant differences at L1 between all groups (p < 0.001). Correlation between Young's modulus (n = 82) and clinical scores was strong (p < 0.001): FFI-pain (r = −0.595); FFI-function (r = −0.567); AOFAS (r = 0.623,). B-US: sensitivity (61%), specificity (95%); SWE sensitivity (85%), specificity (83%). The combination of SWE and B-US increases the sensitivity (100%) with a diagnostic accuracy of 90%. Conclusion: Based on our results, we could show that SWE can improve the diagnostic accuracy in patients with plantar fasciitis compared to B-US. Level of evidence: II
CRIS-Team Scopus Importer:2022-07-20
Keywords: AOFAS Score; FFI; Plantar fasciitis; Shear wave elastography; ultrasound